Implementasi Algoritma RC4 Pada Sistem Informasi Pelaporan DUKCAPIL Provinsi Sulawesi Tengah : Implementation of the RC4 Algorithm in the DUKCAPIL Reporting Information System of Central Sulawesi Province - Iswandi, A.Avri; Ngemba, Hajra; Hendra, Syaiful; Syahrullah; Nouval Daffa Ulhaq, Muhammad (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
The Population and Civil Registration Service Reporting Information System is an important aspect in managing population data at the provincial level. However, data security in these systems is a major concern, given the sensitivity of the personal information contained therein. This research applies the RC4 algorithm to the reporting information system of the Central Sulawesi Province population and civil registration service to improve data security. This research uses a system development method with a case study approach. Researchers implemented the RC4 algorithm on an existing reporting information system and analyzed its impact on data security. Data was collected through interviews with Population and Civil Registration Service officers, observations, and testing system functionality. The applications built are tested using blackbox and crackstation. The results of black box testing show that the application produces the desired output and is in accordance with the function of the application program created. The results of the crackstation test show that the RC4 algorithm was not successfully solved. The research results show that the application of the RC4 algorithm to the reporting information system of the Central Sulawesi Province Population and Civil Registration Service can significantly increase data security. This algorithm is able to encrypt data sent over the network, thereby preventing unauthorized access and misuse of information.